Differences in efficiency, satisfaction and adverse events between self-administered intradermal and nurse-administered intramuscular influenza vaccines in hospital workers. Issue 48 (27th November 2015) - Coleman, Brenda L.; McNeil, Shelly A.; Langley, Joanne M.; Halperin, Scott A.; McGeer, Allison J.
Abstract: Vaccinating healthcare workers against influenza takes tens of thousands of hours of work annually. This study was undertaken to determine the acceptability, success rate, and time to vaccinate healthcare workers in nurse-led groups that self-vaccinated with intradermal influenza vaccine compared with nurse-administered intramuscular vaccine. Methods: Volunteer hospital workers were randomly assigned to groups that either self-administered intradermal influenza vaccine (Intanza ® ) in a nurse-led group or received nurse-administered intramuscular vaccine (Vaxigrip ® ). Research assistants timed vaccination procedures; pre- and post-injection questionnaires assessed acceptability and reactogenicity. Results: 810 adults, 21–69 years of age, from two study sites were vaccinated: 401 self-administered the intradermal vaccine while 409 received their intramuscular vaccine from a nurse. Of those who self-administered for the first time, 98.5% were successful on their first attempt with an additional 1.5% on their second attempt. Acceptability was high: 96% were very or somewhat certain that they administered the vaccine correctly, 83% would choose intradermal influenza vaccine again and of those, 75% would choose self-administration again, if given the choice. It took 51.3–72.6 s per person for the nurses to guide the groups through the self-administration process, which was significantly less time than it took to individually administer the intramuscular vaccines (93.6 s). Conclusion: Self-administration of intradermal influenza vaccine by people working in healthcare settings is a possible alternative to nurse administered vaccinations, with nurse-led group sessions a good way of teaching the technique while being available to respond to unanticipated problems (NCT01665807).